Optimal Microwave Ablation Conditions for the Efficient Lung Carcinoma Treatment - Marija Radmilović-Radjenović; Branislav Radjenović (International Journal of Biomedicine)
The differing dielectric characteristics of healthy and malignant tissues significantly affect the temporal evolution of maximum temperature and the extent of tissue necrosis during the ablation process. Understanding these properties helps optimize MWA parameters, such as power, for better treatment outcomes. This article discusses the results of simulation studies of the effects of microwave ablation (MWA) on lung tumor tissue. Calculations were performed using COMSOL Multiphysics, considering the relative permittivity and conductivity of normal and tumoral lung tissues. The obtained results reveal that ablation zones are predominantly concentrated around the tip and slot of the antenna, with a comparatively minimal backward heating effect. Achieving an optimal target temperature is essential for effective cancer treatment; however, preventing thermal damage to adjacent healthy tissues is equally critical. The results of this study may be useful for optimizing MWA protocols, aiming for minimal invasiveness and enhanced safety in lung cancer treatments. Moreover, the findings emphasize the importance of personalized treatment strategies that consider the unique dielectric characteristics of individual patients' tissues. Overall, this study contributes valuable knowledge to thermal ablation therapies, with significant implications for improving outcomes in lung cancer treatment.